If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -12 = 7m + -41 Reorder the terms: -12 + 2m = 7m + -41 Reorder the terms: -12 + 2m = -41 + 7m Solving -12 + 2m = -41 + 7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7m' to each side of the equation. -12 + 2m + -7m = -41 + 7m + -7m Combine like terms: 2m + -7m = -5m -12 + -5m = -41 + 7m + -7m Combine like terms: 7m + -7m = 0 -12 + -5m = -41 + 0 -12 + -5m = -41 Add '12' to each side of the equation. -12 + 12 + -5m = -41 + 12 Combine like terms: -12 + 12 = 0 0 + -5m = -41 + 12 -5m = -41 + 12 Combine like terms: -41 + 12 = -29 -5m = -29 Divide each side by '-5'. m = 5.8 Simplifying m = 5.8
| a+3a-15=25-2a+6 | | 4/5c-36=8 | | 50-1/3x=70-x | | 3x-5+2x=12-x | | 3x^2-10=-46 | | -29-7x=-5(6x-8) | | 7-12x=3x+32 | | -5q=-30 | | (-4mn^2)(2m^4n^2)= | | 4p+9=1 | | 2x^2+12=-20 | | -4(4v+4)=-112 | | B-4/6=b/-2 | | -6y+7x=30 | | 8y+3=15+7y | | 1-7k=16-4k | | 9x*(-4)= | | 2(3r-v)= | | 8+m=2m-3 | | 2(x-1)=2x+-2 | | x^2+10=-26 | | X-3=6+4 | | 4+2(x+1)+6=14 | | 1+(5q-w)= | | V-(3n+x)= | | 7p-26=107 | | 6-4(x-3)=2x-1 | | x=-2y-7 | | -.2(3+a)=-4 | | (3x-2w)-q= | | X(x-12)+15=-4x | | 16c^4+12b^3=0 |